The Prospective Application of Melatonin in Treating Epigenetic Dysfunctional Diseases - Monayo, Seth Mikaye; Liu, Xin (Frontiers in Pharmacology, 2022)
In the past, different human disorders were described by scientists from the perspective of either environmental factors or just by genetically related mechanisms. The rise in epigenetic studies and its modifications, i.e., heritable alterations in gene expression without changes in DNA sequences, have now been confirmed in diseases. Modifications namely, DNA methylation, posttranslational histone modifications, and non-coding RNAs have led to a better understanding of the coaction between epigenetic alterations and human pathologies. Melatonin is a widely-produced indoleamine regulator molecule that influences numerous biological functions within many cell types. Concerning its broad spectrum of actions, melatonin should be investigated much more for its contribution to the upstream and downstream mechanistic regulation of epigenetic modifications in diseases. It's, therefore, necessary to fill the existing gaps concerning corresponding processes associated with melatonin with the physiological abnormalities brought by epigenetic modifications. This review outlines the findings on melatonin’s action on epigenetic regulation in human diseases including neurodegenerative disease, diabetes, cancer, and cardiovascular diseases. It summarizes the ability of melatonin to act on molecules such as proteins and transcriptional factors which affect the development and progression of diseases.